РОЗВИТОК МОДУЛЬНИХ ЗАСОБІВ ВІДНОВЛЮВАНОЇ ЕНЕРГЕТИКИ - Плескач, Б.М.; Новак, Є.В. (Інститут електродинаміки Національної академії наук України, 2024)
The development of modular power supplies, which are used as the main or reserve source of electricity in hard-to-reach places, or places with difficult climatic conditions for full or partial coverage of electrical loads of individual industrial and social facilities, has been studied. The main attention is paid to mobile autonomous solar and wind power plants (MASVES). The features of construction are considered and a drawing of the general appearance of such a power plant is given. Ref. 5, figure.